2009
DOI: 10.1111/j.1467-2995.2009.00477.x
|View full text |Cite|
|
Sign up to set email alerts
|

A study of cardiovascular function under controlled and spontaneous ventilation in isoflurane–medetomidine anaesthetized horses

Abstract: Objective  To determine, in mildly hypercapnic horses under isoflurane–medetomidine balanced anaesthesia, whether there is a difference in cardiovascular function between spontaneous ventilation (SV) and intermittent positive pressure ventilation (IPPV). Study design  Prospective randomized clinical study. Animals  Sixty horses, undergoing elective surgical procedures under general anaesthesia: ASA classification I or II. Methods  Horses were sedated with medetomidine and anaesthesia was induced with ketamine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
35
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 27 publications
0
35
0
Order By: Relevance
“…A few reasons might have contributed to these results: a) the horses were mechanically ventilated to maintain normocapnia; b) the horses were not subjected to noxious stimulation. In horses anesthetized under mechanical ventilation, cardiovascular depression is expected to occur unless the ventilation is adjusted to allow mild hypercapnia, considered as PaCO2 values of 50-60mmHg (KALCHOFNER et al, 2009). Also, it has been reported that in horses anesthetized for surgical procedures, DBT was effective in improving cardiovascular performance (DE VRIES et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…A few reasons might have contributed to these results: a) the horses were mechanically ventilated to maintain normocapnia; b) the horses were not subjected to noxious stimulation. In horses anesthetized under mechanical ventilation, cardiovascular depression is expected to occur unless the ventilation is adjusted to allow mild hypercapnia, considered as PaCO2 values of 50-60mmHg (KALCHOFNER et al, 2009). Also, it has been reported that in horses anesthetized for surgical procedures, DBT was effective in improving cardiovascular performance (DE VRIES et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have recognized these detrimental effects of mechanical ventilation in horses (Hodgson et al 1986, Steffey et al 1992, Mizuno et al 1994, Edner et al 2005) while others have found no or minimal detrimental effects on cardiovascular parameters when using IPPV with or without PEEP (Swanson and Muir 1988, Wettstein et al 2006, Bringewatt et al 2010, Hopster et al 2011, Ambrosio et al 2013. One other study found these cardiovascular effects to be negligible when providing mild hypercapnia (Kalchofner et al 2009). Whether and to which degree the cardiovascular system will be impaired appears to be greatly influenced by pressures used and the time over which high PIP and PEEP pressures are applied.…”
Section: Introductionmentioning
confidence: 99%
“…It supports lung function by eliminating carbondioxide and allowing oxygenisation of arterial blood. It increases tidal volume and enables atelectatic alveoli to regain their function 2,3,[5][6][7] .…”
mentioning
confidence: 99%
“…Over-inflation of the alveoli leads to formation of pulmonary interstitial emphysema, pneumomediastinum and pneumothorax 6,8 . Due to increasing thoracic pressure, right ventricular dysfunction, altered left ventricular distensibility and low cardiac output, IPPV decreases venous return to the heart 2,3,5,6,9 .…”
mentioning
confidence: 99%
See 1 more Smart Citation